NC palladacycles in the Heck arylation of ethylene: synthesis, structure and their reactivity - Atla, Shashi B.; Kelkar, Ashutosh A.; Puranik, Vedavati G.; Bensch, Wolfgang; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2009)
Monomeric cyclopalladated complexes with NC coordination using ligands 2-phenylpyridine, 2-phenylquinoline, 8-methylquinoline have been synthesized and the structures have been determined by single crystal X-ray structure analysis. The crystal structures of monomeric palladacycles prepared using benzophenone oxime, and 2-phenylpyridine have also been determined. The use of these complexes in the Heck arylation of ethylene with 2-bromo-6-methoxynaphthalne (BMN) to give 2-vinyl-6-methoxynapthalene which is an intermediate for the synthesis of anti-inflammatory drug Naproxen has been examined and also arylation of ethylene with 3-bromo-benzophenone and 4-bromo-isobutylbenzene was investigated. These palladacycles with NC coordination show excellent catalytic activity with a TOF > 4000 h (1). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aryl propionic acids; Arylation; Palladacycle